2021
DOI: 10.1002/ptr.7047
|View full text |Cite
|
Sign up to set email alerts
|

The effect of soy isoflavones and soy isoflavones plus soy protein on serum concentration of tumor necrosis factor‐α? A systematic review and meta‐analysis of randomized controlled trials

Abstract: In this study, we summarized the effect of soy isoflavones and soy isoflavones plus soy protein on serum concentration of tumor necrosis factor-alpha (TNF-α) among adult participants. We systematically searched Scopus, ISI Web of Science, Cochrane Library, PubMed, and clinicaltrials.gov for articles published up to May 2020. Effect size was calculated by mean change from baseline of TNF-α concentrations and its standard deviation (SD) for intervention and comparison groups. If the heterogeneity test was statis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Soy milk digested with pepsin and pancreatin inhibited the production of IL-1β, nitric oxide, nitric oxide synthase, and COX-2 (Chatterjee et al, 2018;González-Montoya, Hernández-Ledesma, Silván, Mora-Escobedo, & Martínez-Villaluenga, 2018). A meta-analysis, which analyzed findings of 18 clinical trials, showed that soy isoflavones and soy isoflavones plus soy protein had no significant effects on serum TNF-α (Hariri, Baradaran, & Gholami, 2021). In a double-blind, randomized controlled study, 63 overweight or obese individuals were supplemented with 2500 mg soybeans daily or 2500 mg starch in the control group for 8 weeks.…”
Section: Soymentioning
confidence: 99%
“…Soy milk digested with pepsin and pancreatin inhibited the production of IL-1β, nitric oxide, nitric oxide synthase, and COX-2 (Chatterjee et al, 2018;González-Montoya, Hernández-Ledesma, Silván, Mora-Escobedo, & Martínez-Villaluenga, 2018). A meta-analysis, which analyzed findings of 18 clinical trials, showed that soy isoflavones and soy isoflavones plus soy protein had no significant effects on serum TNF-α (Hariri, Baradaran, & Gholami, 2021). In a double-blind, randomized controlled study, 63 overweight or obese individuals were supplemented with 2500 mg soybeans daily or 2500 mg starch in the control group for 8 weeks.…”
Section: Soymentioning
confidence: 99%
“…For example, ISF suppresses arterial stiffness, regulating intestinal flora and mimicking estrogen via its special structure to affect the physiological state of animals [107,108]. In addition, recent studies showed that ISF demonstrated immune modulation, anti-inflammatory, and antiviral properties [56][57][58]109,110]. Rochell et al evaluated the effects of dietary soybean meal (SBM) on the growth performance and immune response of pigs infected with PRRSV [57].…”
Section: Porcine Reproductive and Respiratory Syndrome Virusmentioning
confidence: 99%